Attitudes of employees towards HIV/AIDS within the Department of Environmental Affairs and Tourism (an employee assistance study) - amngadi@cipro.gov.za (University of Pretoria, 2013)
Dissertation (MSocSci (EAP))--University of Pretoria, 2006.